Strategi Guru PAI dalam Menghadapi Perbedaan Kemampuan Peserta Didik - Dwiyana Ndari Saputri; Serli Notapiya; Taufik Rahman (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
This study examines the strategies of Islamic Education (PAI) teachers in addressing differences in student abilities. Teachers employ individual and group approaches, along with methods such as lectures, discussions, and exercises to enhance student absorption. Factors influencing these differences include family background, interest, and environment. The study aims to identify how teachers motivate students and create a conducive learning environment.